Acute mortality in California tiger salamander (Ambystoma californiense) and Santa Cruz long-toed salamander (Ambystoma macrodactylum croceum) caused by Ribeiroia ondatrae (Class: Trematoda). (December 2021) - Keller, Saskia; Roderick, Constance L.; Caris, Christopher; Grear, Daniel A.; Cole, Rebecca A.
Abstract: In early September 2019, a morbidity and mortality event affecting California tiger salamanders ( Ambystoma californiense ) and Santa Cruz long-toed salamanders ( Ambystoma macrodactylum croceum ) in late stages of metamorphosis was reported at a National Wildlife Refuge in Santa Cruz County, California, U.S.A. During the postmortem disease investigation, severe integumentary metacercarial (Class: Trematoda) infection, associated with widespread skin lesions, was observed. Planorbid snails collected from the ponds of the refuge within seven days of the mortality event were infected with Ribeiroia ondatrae, a digenetic trematode that can cause malformation and death in some amphibians. We suggest sustained seasonal high-water levels due to active habitat management along with several years of increased rainfall led to increased bird visitation, increased over-wintering of snails, and prolonged salamander metamorphosis, resulting in a confluence of conditions and cascading of host-parasite dynamics to create a hyper-parasitized state. Graphical abstract: Image 1 Highlights: Mortality event in wild endangered salamanders in California. Infection with Ribeiroia ondatrae caused severe fatal skin lesions. Sustaining water levels may increase parasite transmission.